Serapan Hara N, P, K, dan Hasil Berbagai Varietas Tanaman Padi Sawah dengan Pemberian Amelioran Ion Cu, Zn, Fe pada Tanah Gambut - Zahrah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
This research was conducted in the Experimental Field, Faculty of Agriculture, Riau Islamic University and SoilLaboratory, BPTP Riau Province from August to December 2007. The research aim to study the effect of Cu2+, Zn2+,Fe3+ ameliorant addition in peat to N, P, K uptake and rice yield of various varieties. The experimental with CompletelyRandomized Design for Factorial 4 x 4 were used. The first factor was ameliorant addition, consists of four levels(Cu2+; Zn2+; Fe3+) and second factor based on varieties, consists of four levels (PB-42, IR-64, Ciherang, Cisantana).The result of research indicates that: (1) Interactian effect of treatment was significant to N, P, K uptake, productivestem, weight of dried seed, and weight of 1000 seeds, (2) The best treatment was Cu2+ ameliorant on IR-64 withuptake of N ( 254,0 mg/plant), P (32,8 mg/plant), K (76,0 mg/plant), productive stem (30,0 stems/plant), weight ofdried seed (63,9 g/plant), weight of 1000 seeds (23,7 g).